Is There a Minimum Effective Dose for Vascular Occlusion During Blood Flow Restriction Training? - Das, Arpan; Paton, Bruce (Frontiers in Physiology, 2022)
Background Blood flow restriction (BFR) training at lower exercise intensities has a range of applications, allowing subjects to achieve strength and hypertrophy gains matching those training at high intensity. However, there is no clear consensus on the percentage of limb occlusion pressure [%LOP, expressed as a % of the pressure required to occlude systolic blood pressure (SBP)] and percentage of one repetition max weight (%1RM) required to achieve these results. This review aims to explore what the optimal and minimal combination of LOP and 1RM is for significant results using BFR. Method A literature search using PubMed, Scopus, Wiley Online, Springer Link, and relevant citations from review papers was performed, and articles assessed for suitability. Original studies using BFR with a resistance training exercise intervention, who chose a set %LOP and %1RM and compared to a non-BFR control were included in this review. Result Twenty-one studies met the inclusion criteria. %LOP ranged from 40 to 150%. %1RM used ranged from 15 to 80%. Training at 1RM ≤20%, or ≥ 80% did not produce significant strength results compared to controls. Applying %LOP of ≤50% and ≥ 80% did not produce significant strength improvement compared to controls. This may be due to a mechanism mediated by lactate accumulation, which is facilitated by increased training volume and a moderate exercise intensity. Conclusion Training at a minimum of 30 %1RM with BFR is required for strength gains matching non-BFR high intensity training. Moderate intensity training (40–60%1RM) with BFR may produce results exceeding non-BFR high intensity however the literature is sparse. A %LOP of 50–80% is optimal for BFR training.